Foresight for Science and Technology Priority Setting in Korea - Moonjung Choi; Han-Lim Choi (Foresight and STI Governance, 2015)
The main purpose of Technology Foresight (TF) in Korea is to predict the development of S&T and use the results in developing S&T policies. However, informing the public about what the future holds based on the development of S&T is an equally important role of TF.Since the introduction of the first TF in 1994, Korea has conducted four such studies. TF in Korea has become a key process in setting S&T policy, such as the Science and Technology Basic Plan (S&T Basic Plan). The S&T Basic Plan determines the national strategic technologies by reflecting on future technology. The S&T Basic Plan is a mandatory legal planning process established every five years by the Korean government. It is the top-level policy document affecting S&T-related policy making in Korea.TF in Korea primarily utilizes the Delphi method. The third and fourth TFs have strengthened the links between S&T and society by determining future technologies capable of solving future needs. The fourth TF presented scenarios and special illustrations to show members of the public the future technologies and their implications for society. Additionally, the fourth round of TF analyzed the potential negative impacts of future technologies.